Liquid phase selective hydrogenation of cinnamaldehyde over copper supported catalysts - Gutierrez, Victoria Soledad (2012)
The selective hydrogenation of cinnamaldehyde is carried out in a batch reactor, at 100 °C and 1 MPa of H 2 using isopropyl alcohol as the solvent, over a series of copper supported catalysts: Cu/Al 2O 3, Cu/SiO 2 Cu/MCM-48, Cu/CeO 2 and Cu/α-Fe 2O 3. The selectivity of the samples is compared with that corresponding to Pti/SiO 2. Reduced Cu/Al 2O 3 and Cu/SiO 2 showed lower selectivity to the cinnamyl alcohol (16-22%) than Pt/SiO 2 (35%), at 15% of conversion. Following a calcination at 300 °C both, activity and selectivity of copper catalysts were increased. The calcined surface would hydrogenate CO bond by hydrogen transfer from the solvent. TPR, XRD and FTIR of adsorbed CO showed that Cu (I) species are stabilized on the mesoporous structure of MCM-48. This particular feature renders Cu/MCM-48 a selective catalyst, reaching high selectivity values (51%, at 15% of conversion). Cu/CeO 2 and Cu/α-Fe 2O 3 showed higher selectivity than Pt based catalyst due to a promotion of the catalytic properties of copper by reduced support species.